Infectious Bovine Rinotracheitis (IBR) on Livestock Breeding Institution in Indonesia - Sudarisman . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
The government livestock breeding farm in Indonesia had had a potential role for preventing the animals to spread the disease of Infectious Bovine Rhinotracheitis. Prevalence of IBR have increased according by the time being in dairy and beef cattle. To anticipate the spread of the disease, government livestock breeding farm should be free of IBR disease, serologically and through isolation of the agent. As an alternative to control the disease, early warning detection of the infections and contamination on the product of artificial insemination centre and embryo transfer institution in Indonesia is more esential to use PCR as a toll to detect every batch of the products. Vaccination is one of the choise to prevent the disease in the field, especially in the area which the disease as an endemic, according to economical impact of the disease.   Key words: IBR, livestock breeding farm, PCR, product